City Panoramas From Anatolia in Eugène Flandin's Engravings - Çelık, Dilan; Güzel, Eylem (Fırat University, 2023)
The Ottoman Empire has been an irresistible center of attraction for Western travelers and artists for centuries with its vast lands. The geography of the Empire, where centers such as Istanbul were the focus of attention at the beginning, became a more easily accessible place thanks to the technological opportunities that developed in the 18th and 19th centuries. In addition, cities in different regions such as İzmir, Aydın, Van and Erzurum within the borders of the imperial geography, which were in the interest of the Westerners with the influence of art movements such as Romanticism and Orientalism that took place in Europe's own internal dynamics during this period, began to take place in the works of wandering artists. One of the prominent names among Western artists who visited a large part of Anatolia, especially Istanbul, is the French-born Orientalist painter Eugène Flandin. City panoramas, which include topographic views of cities, have an important place among the engravings made by the traveling artist. In this study; The city panoramas that Flandin realized after his travel and evaluated in the type of topographic landscape will be discussed. you can see the features. In the light of these sources, it is extremely useful to reveal the original situations of our cultural values that have disappeared or changed.

Osmanlı İmparatorluğu yayıldığı geniş toprakları ile yüzyıllar boyunca Batılı seyyah ve sanatçılar için dayanılmaz bir cazibe merkezi olmuştur. Başlangıçta İstanbul gibi merkezlerin ilgi odağı olduğu İmparatorluk coğrafyası, 18. ve 19. yüzyıllarda gelişen teknolojik imkânlar sayesinde, daha kolay ulaşılabilir bir yer haline gelmiştir. Ayrıca bu dönemde Avrupa’nın kendi iç dinamiğinde meydana gelen Romantizm, Oryantalizm gibi sanat akımlarının etkisiyle Batılıların ilgi alanına giren imparatorluk coğrafyasının sınırları dâhilindeki İzmir, Aydın, Van ve Erzurum gibi farklı bölgelerdeki kentler de gezgin sanatçıların çalışmalarında yer bulmaya başlamıştır. Başta İstanbul olmak üzere Anadolu’nun büyük bir kısmını ziyaret eden Batılı sanatçılar arasında öne çıkan isimlerden biri Fransız asıllı Oryantalist ressam Eugène Flandin’dir. Gezgin sanatçının gerçekleştirdiği gravürler arasında şehirlerin topoğrafik görünümlerini içeren kent panoramaları önemli bir yer tutmaktadır. Bu çalışmada; Flandin’in seyahati sonrasında gerçekleştirdiği ve topoğrafik manzara türünde değerlendirilen kent panoramaları ele alınacaktır. Belgesel ve sanatsal açıdan incelenecek gravürlerde şehirlerin günümüzde geçirdiği dönüşüm ve fiziki değişimler takip edilerek, dönemin baskın sanat akımlarından Romantizm ve Oryantalizm sanat üsluplarının etkisi de gravürler üzerinde değerlendirilmeye çalışılacaktır.
EUGÈNE FLANDİN’İN GRAVÜRLERİNDE ANADOLU’DAN KENT PANORAMALARI